Produção de enzimas lignocelulolíticas por trametes versicolor e trichoderma asperellum utilizando bagaço de uva e farelo de trigo como substratos - Corrêa, Anderson Gabriel (2023)
The use of lignocellulosic biomass as a source of carbon in fermentation processes for enzymatic prospecting has been the subject of several studies today. The present work intended to evaluate the synthesis of cellulase, xylanases and laccase, by the fungal strains Trametes versicolor and Trichoderma asperellum, in monoculture and consortium, through solid state fermentation, using grape pomace and wheat bran as a carbon source. The best ß-glucosidase production of 218.91 U/g was treated using the T. versicolor fungus with wheat bran as substrate. The production of xylanases showed activity peaks of 19.39 U/g for ß-xylosidase and xylanase of 170.28 U/g, both in processes with wheat bran and fungal consortium. And the production of laccase, fed 16.5 U/g of activity with mixed substrate, containing grape pomace and wheat bran, with the microorganism T. versicolor. The obtained data demonstrated that the carbon sources used in the fermentation processes offer nutritional and growth support to the filamentous fungi used, which, in turn, were good enzyme inducers, with emphasis on the production of ß-glucosidase and xylanase.